Peningkatan Kualitas Pembelajaran Melalui Manajemen Berbasis Sekolah di TK ABA Piyaman III - Pramitajati, Ika Nuari Pramitajati; Saryanto (Media Manajemen Pendidikan, 2025)
This research aims to analyze the implementation of School Based Management (MBS) in improving the quality of learning at Kindergarten ABA Piyaman III Wonosari. The research focus includes stakeholder participation, learning innovation, and transparency of school management. This research uses a school action research method with a qualitative approach which was carried out in two cycles in the 2024 academic year. Data was collected through observation, interviews and document analysis. The research results show an increase in stakeholder participation from 72% to 78%, child development in cognitive aspects from 70% to 77%, social-emotional from 73% to 80%, and physical-motor from 75% to 82%. Transparency and accountability in school management also increased from 75% to 82%. The successful implementation of SBM is supported by the use of information technology in school communication, adjusting schedules with parents, and implementing innovative learning methods. This research contributes to the development of SBM implementation models at the kindergarten education level, especially in semi-urban areas.